Determinants of quality of life person with disabilities in Malaysia - Alias Abd Aziz,; Rohana Jani,; Hanira Hanafi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
To maximize the quality of life (QoL) among persons with disabilities (PWDs) in Malaysia, it is important to identify factors that are strongly associated with the QoL of PWDs. The aim of this study is to identify the determinants of QoL among PWDs in Malaysia. A cross-sectional study approach was applied covering 340 participants with hearing impairments, visual impairments, and physical disabilities. A multiple regression analysis was performed to determine the determinants of QoL. The seven QoL domains namely physical health, psychological, social relationships, environment, discrimination, autonomy, and inclusion were considered as dependent variables while demographic profile, socio-economic status, and disability history were considered independent variables. The contribution of independent variables to most of the QoL domains was modest. This study found that type of disabilities is a significant determinant for physical health, psychological, environment, discrimination, and inclusion domains. Meanwhile, the level of education is a significant determinant in the environment and autonomy domain. It was also found that age group is a significant determinant in the psychological domain. Meanwhile, employment status is a significant determinant in physical health domains. However, self-rated health is not significant in the discrimination domain. Both PWDs with good health conditions or PWDs with unhealthy conditions face the same experience of discrimination. These findings supplement the existing knowledge and contribute to future research, service planning initiatives, public education, and policy formulation. Furthermore, this study may aid social service stakeholders in evaluating the effectiveness of current activities and identifying trends for future planning.